Building a Resilient Global Economy - Purohit, Brijesh C. (Utan Kayu Publishing, 2023)
In this paper we discuss the concept of economic resilience which is the ability of the economy to respond to a economic shock and recover at the fastest pace. We take into consideration the survey reports of RBI. The six surveys recently published by RBI depicts that India is becoming more resilient economy. The concept discussed only at the country level by earlier international studies although indicate India’s relative international ranking as 65. We develop a state level index by appropriate modification of the concept of economic resilience to the state level context. Thus, our state level resilience index depicts Maharashtra and Jharkhand as highest and lowest resilient States respectively. However, our state level indices are in the nascent State and future research may be more useful to further develop it for more confident application in analytical studies.